Intravaginal probiotics before embryo transfer do not improve pregnancy rates in recurrent implantation failure cases: An RCT - Mina Naghi Jafarabadi; Farnaz Hadavi; Maedeh Ahmadi; Masoumeh Masoumi; Sara Zabihzadeh (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Considering the considerable influence of the vaginal microbiome on endometrial receptivity and embryo implantation, we hypothesized that cases of recurrent implantation failure (RIF) might benefit from the intravaginal probiotic administration. Objective: Evaluation of the effects of intravaginal probiotic administration before frozen embryo transfer (FET) on the rates of pregnancy and the status of vaginal lactobacillary flora in cases of RIF. Materials and Methods: This was a randomized, parallel-group, clinical trial conducted at an infertility clinic in Tehran, Iran between January 2021 and September 2022. A total of 166 reproductive-aged women with a history of unexplained RIF were randomly assigned to either the probiotic group or the control group (n = 83/each group). The probiotic group received intravaginal probiotics (LactoVagⓇ) daily for 2 wk from the second day of the menstrual cycle along with the routine treatment of FET. The control group received only the routine treatment of FET. The primary outcome was the chemical pregnancy rate, and the secondary outcomes were the clinical pregnancy rate and the status of vaginal lactobacillary flora. Results: A total of 163 participants were included in the final analysis. The probiotic group had a slightly higher chemical pregnancy rate than the control group (39.02% vs. 33.33%), but the difference was not statistically significant (risk ratio: 1.71, 95% CI: 0.77-1.76; p = 0.449). The clinical pregnancy rate was also non-significantly higher in the probiotic group than the control group (37.80% vs. 33.33%; RR: 1.14, 95% CI: 0.76-1.74; p = 0.623). Conclusion: Intravaginal probiotic administration did not significantly improve the pregnancy rates in RIF cases undergoing FET. Further studies are needed to explore the optimal dose, duration, and timing of probiotic administration, as well as the mechanisms of action and the potential adverse effects of probiotics on the vaginal microbiome and the implantation process.